Implementing New Manufacturing Technology: The Related Effects of Technology Characteristics and User Learning Activities - Aiman‐Smith, Lynda; Green, Stephen G. (Academy of Management Journal, 2002)
This study of 157 users of new technologies implemented in manufacturing demonstrates complex relationships between technology characteristics, users' learning activities, and implementation outcomes. Technology characteristics affected both implementation outcomes and users' learning activities. On balance, technology characteristics explained more variance in user ?speed to competence? and the quality of learning activities explained more variance in user satisfaction. Technology and learning activities independently affected implementation outcomes, with no evidence of mediation or moderation.